Achieving remarkable enhancement on electromagnetic shielding performance in multi-walled carbon nanotube/polydimethylsiloxane composites via adding a small amount of metal micro-particles as scattering points. (November 2022) - Wang, Ye; He, Qian-Ming; Gao, Ya-Nan; Yue, Tian-Ning; Wang, Ming
Graphical abstract: Highlights: Composites exhibit high EMW SE by adding a small amount of μ-Cu particles. The μ-Cu particles act as scattering points for EMWs in the composites. Propagation paths of EMWs in samples increase via adding scattering points. Scattering point amounts and electrical conductivity are vital factors to EMW SE. The simulation results show obvious influence of μ-Cu particles on EMWs. Abstract: Herein, a small amount of copper micro-particles (μ-Cu particles) were added into the multi-walled carbon nanotube/polydimethylsiloxane (PCNT) composites acting as electromagnetic wave (EMW) scattering points to enhance their EMW shielding performance. The μ-Cu particles/PCNT (PCNTC) composites were prepared by solvent-assisted and hot-press molding methods. Thanks to the high scattering of μ-Cu particles, which increases propagation paths of EMW inside the composites, remarkable enhancement on EMW shielding property could be achieved by adding small amount of conductive μ-Cu particles into the composites. The effects of the diameter and content of μ-Cu particles on the EMW SE of the composites were investigated in this study. Furthermore, the shielding mechanism of the composite to EMW was simulated and verified by an electromagnetic simulation. In addition, the reflection loss (SER ) and reflectivity coefficient ( R ) were used to evaluate the shielding mechanism of the composites. The composites had low SER of 1.6 dB and R of 0.29 values, suggesting an absorption-type shielding mechanism.